The status of financial inclusion, regulation, and education in India - Abheek Barua; Rajat Kathuria; Neha Malik (Asian Development Bank Institute (ADBI), 2016)
India's financial inclusion agenda has witnessed a paradigm shift over the last decade, away from an emphasis on credit to a more comprehensive approach toward financial services (e.g., opening bank accounts and offering basic financial products, such as insurance). This paper describes the structure of banking and microfinance institutions in India relevant to the developing model of financial inclusion, as well as relevant regulatory structure and modes of delivery. It explains the current state of financial inclusion, as well as regulatory changes necessary to make the new architecture for inclusion viable, including a critique of some of the recommendations of the Mor Committee on Comprehensive Financial Services for Small Businesses and Low-Income Households. The paper then reviews modes of delivery and the regulatory structure being contemplated or recently introduced. It assesses the suitability objective envisaged as critical for inclusion, associated challenge of revamping consumer protection laws, and imperative of improving financial literacy. The paper also discusses the case of micro, small, and medium-sized enterprises in the given context.
Keywords: G21; G28; L53; O16; 330; India's financial inclusion; microfinance institutions; financial literacy; consumer protection laws